PERAN LITERASI DIGITAL DALAM MENINGKATKAN KEMAMPUAN BER-PIKIR KRITIS SISWA SD - Apri Lusi, Seska; Ariri, Fikah; Rahmanda, Natasya; Tri Wahyu Nopita Sari, Ratih; Darmayanti, Nadila; Almubarok, Ahmad; Chandra; Habibi, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of digital literacy still faces challenges such as limited facilities, internet access, and technological competency for both teachers and students. Therefore, digital literacy plays a crucial role in creating a more effective, innovative, and 21st-century learning process. It also supports the development of independent, adaptive students who are ready to face the challenges of future technological developments and are highly competitive in a rapidly evolving global environment. The purpose of this study is to explore the role of digital literacy in improving the critical thinking skills of elementary school students. The method used is a literature study with a descriptive qualitative approach through the analysis of various sources such as journals, books, and relevant scientific articles. The findings of this study indicate that digital literacy makes a positive contribution to improving students' critical thinking skills, as seen in their skills in analyzing, evaluating, and solving problems based on information obtained from various digital sources. In addition, the use of interactive digital media in learning can increase student participation, learning interest, and activeness. The development of digital technology has brought about a significant transformation in the education sector, especially at the elementary school level, which requires students to have digital literacy skills and critical thinking abilities.